SUSTAINABILITY OF SAMPYONG: REVITALIZATION EFFORT OF A PERFORMANCE ART TO A MARTIAL ART - Nurhayati Nurhayati; Sukirno Sukirno; Latifah Ratnawati (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to revitalize sampyong performance art to sampyong martial art through receptive response of the community. The receptive response of the community means how people’s perception towards the existence of sampyong and how people’s reaction towards the sustainability of sampyong performance art to sampyong martial art. This study used mixed method procedures of Cresswell’s instruction. The data collection technique was done through questionnaires and focus group discussion. The data of questionnaires show that of 55% the youth were not acquintanced with sampyong. About 86% of the youth agreed whether sampyong turned out to be a nationally well-known martial art. From the focus group discussion data, it was found that respondents agreed that sampyong performance art become a martial art of sampyong along with its particular characteristics. These characteristics change the old paradigm to a new paradigm which includes names, functions, players, places, arenas, medical team, cutting-ices preparation, matches rules, costumes, judges, properties, music, and prologues. The pilot project implementation of revitalization efforts by changing sampyong from performing art to martial art has been carried out to prospective teacher students at Universitas Sriwijaya.